2021
DOI: 10.1093/milmed/usaa361
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Surgery at War: A Scoping Review of Current Conflicts

Abstract: Introduction The scope of military plastic surgery and location where care is provided has evolved with each major conflict. To help inform plastic surgeon utilization in future conflicts, we conducted a review of military plastic surgery-related studies to characterize plastic surgeon contributions during recent military operations. Materials and Methods Using a scoping review design, we searched electronic databases to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…[ 8 ] According to Fox et al, procedures performed by plastic surgeons include delayed primary suturing, tangential excision of necrotic tissue, skin graft or flap coverage, and release of secondary scar contractures to manage soft tissue injuries. [ 22 ] In our study, we found a strong relationship between the face and external injuries and plastic surgery, with the open reduction in the face area and the dressing in the external area being the most frequently performed procedures.…”
Section: Discussionmentioning
confidence: 72%
“…[ 8 ] According to Fox et al, procedures performed by plastic surgeons include delayed primary suturing, tangential excision of necrotic tissue, skin graft or flap coverage, and release of secondary scar contractures to manage soft tissue injuries. [ 22 ] In our study, we found a strong relationship between the face and external injuries and plastic surgery, with the open reduction in the face area and the dressing in the external area being the most frequently performed procedures.…”
Section: Discussionmentioning
confidence: 72%
“…The current imbalance of support in the form of government funding to the multidisciplinary approach remains a subject of criticism. Indeed, plastic surgeons are equipped with the skill sets required to address traumatic injuries, including management of soft-tissue injury, fractures in facial structures, neurovascular injury, and salvaging extremities [5][6][7][8]. Such critical role of plastic surgeons in trauma care is underrecognized due to regulations preventing them from serving as dedicated specialists, thereby depriving them of commensurate compensation.…”
Section: Plos Onementioning
confidence: 99%
“…However, thanks to much academic and clinical endeavor, plastic surgeons today play an integral role over a diversity of fields, from reconstructive to aesthetic surgery. Plastic surgeons are equipped with the skill sets required to address traumatic injuries, including management of soft-tissue injury, fractures in facial structures, neurovascular injury, and salvaging extremities [5][6][7][8]. Developments in diagnostic and therapeutic devices over the past 50 years, such as the evolution of imaging, microscope, dressing materials, and surgical instruments are also conducive to plastic surgeons' role in treating trauma patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant public health implications of violence-related limb injuries in conflict zones, there is a paucity of research focusing on the role of ortho-plastic teams in their management. Most existing data are based on studies conducted on military personnel or in high-income countries where resources are more readily available [ 13 , 14 ]. Furthermore, the unique challenges of conflict zones, such as the Gaza Strip, highlight the urgent need for building evidence out of these contexts.…”
Section: Introductionmentioning
confidence: 99%